2022
DOI: 10.3390/s22249812
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Functional Electrical Stimulation Controlled by a System of Sensors for the Lower Limbs: A Systematic Review

Abstract: In the field of transcutaneous functional electrical stimulation (FES), open-loop and closed-loop control strategies have been developed to restore functions of the lower limbs: walking, standing up, maintaining posture, and cycling. These strategies require sensors that provide feedback information on muscle activity or biomechanics of movement. Since muscle response induced by transcutaneous FES is nonlinear, time-varying, and dependent on muscle fatigue evolution, the choice of sensor type and control strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 135 publications
0
1
0
Order By: Relevance
“…The combination of hypertonic flexion and somatosensory abnormalities in the lower limbs is often manifested as knee extension and functional leg extension difficulties, severely limiting the functional workspace of patients [ 25 ]. FES, which is a method of inducing muscle contraction to assist or restore motor function, has been applied in gait rehabilitation in patients with gait defects after neurological disorders [ 26 ]. Recently, a study reported the role of FES in the common peroneal nerve through the long-term use of the foot drop stimulator significantly.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of hypertonic flexion and somatosensory abnormalities in the lower limbs is often manifested as knee extension and functional leg extension difficulties, severely limiting the functional workspace of patients [ 25 ]. FES, which is a method of inducing muscle contraction to assist or restore motor function, has been applied in gait rehabilitation in patients with gait defects after neurological disorders [ 26 ]. Recently, a study reported the role of FES in the common peroneal nerve through the long-term use of the foot drop stimulator significantly.…”
Section: Discussionmentioning
confidence: 99%